INTEGRATION OF NATURAL SCIENCES IN SCHOOL CHEMISTRY CLASSES - Rahmonova U.T.; Yo’lchiyeva Nodira Ravshan qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article is based on the materials used in the framework of the PISA research on interdisciplinary integration, it contains the content of the international PISA study, the main concepts and tasks related to the direction of literacy assessment in natural sciences, their description and solutions.